Immunohistochemical Expression of Bcl3 in Human Breast Carcinoma - Al-Jubouri, Reyadh; Al-Rawi, Faeza; Al-Khafaji, Ali (Iraqi Journal of Science, 2023)
B-Cell lymphoma 3 is a putative proto-oncogene that involved in central oncogenic pathways that regulate cell death, apoptosis and metastatic of tumor cells so it could be important as a target to validation as a diagnostic or prognostic marker in these tumors. This study revealed positive expression of Bcl3 in (76.6%) of 47 cases infiltrating ductal carcinoma and (61.7%) of positive were strong positive. These results showed no significant association of immunohistochemical expression of Bcl3 with clinicopathological features as well no relation with immunohistochemical expressions of estrogen rreceptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER-2/neu).